Breeding of ornamental plants in Russia - R. S. Rakhmangulov; N. G. Tikhonova (Биотехнология и селекция растений, 2022)
The breeding of ornamental plants as a branch of crop production is an integral part of the set of measures aimed at obtaining a wide range of different plants with high decorative characteristics. The main objective of this branch is the creation of plants that are attractive to the consumer and commercially characterized by such valuable biological features as adaptability, resistance to diseases, pests, frost and others. Most ornamental plant varieties were bred by means of traditional breeding methods such as selection, distant hybridization, clone breeding, radiation and chemically induced mutagenesis. However, the use of traditional breeding tools is limited by the potential for intraspecific variability. The development of modern biotechnological and genetic approaches to the breeding of new varieties has made it possible to modify the plant genotype at a qualitatively new level. The present review covers the directions in and methodology of modern ornamental plant breeding in Russia, ways of mobilizing the genetic resources of the main ornamental crops such as rose, clematis, canna, chrysanthemum, pelargonia, iris, daylily, tulip, lilac, and rhododendron. Aslo, the review offers examples of ornamental plant breeding work uderway in the leading specialized scientific institutions such as the Russian State Agrarian University – the K.A. Timiryazev Moscow Agricultural Academy, I.V. Michurin Federal Research Centre, Nikitsky Botanical Gardens – National Scientific Center of the RAS, Subtropical Scientific Center of the Russian Academy of Sciences, Botanical Garden of the M.V. Lomonosov Moscow State University, All-Russian Scientific Research Institute of Tobacco, Mahorka and Tobacco Products. The world and Russian flower and ornamental plants markets, the problem and methods of resolving the issue of quality import substitution, and prospects for the development of floriculture in Russia in the foreseeable future are also briefly considered.